2018
DOI: 10.1186/s12913-018-2974-4
|View full text |Cite
|
Sign up to set email alerts
|

Porous safety net: catastrophic health expenditure and its determinants among insured households in Togo

Abstract: BackgroundIn Togo, about half of health care costs are paid at the point of service, which reduces access to health care and exposes households to catastrophic health expenditure (CHE). To address this situation, the Togolese government introduced a National Health Insurance Scheme (NHIS) in 2011. This insurance currently covers only employees and retirees of the State as well as their dependents, although plans for extension exist. This study is the first attempt to examine the extent to which Togo’s NHIS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 45 publications
9
43
2
Order By: Relevance
“…Therefore, it is necessary to further focus policy efforts on elderly and impoverished households, such as increasing welfare subsidies or extending medical assistance programs to enhance financial protection and reduce CHE. Previous reports described significant associations between the type of healthcare facility and CHE [28,35]. Our study also found that seeking inpatient services in second-level hospitals or above increased CHE incidence and intensity, which suggests that higher medical costs of high-level hospitals and hospitalization may result in more catastrophic health expenses.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, it is necessary to further focus policy efforts on elderly and impoverished households, such as increasing welfare subsidies or extending medical assistance programs to enhance financial protection and reduce CHE. Previous reports described significant associations between the type of healthcare facility and CHE [28,35]. Our study also found that seeking inpatient services in second-level hospitals or above increased CHE incidence and intensity, which suggests that higher medical costs of high-level hospitals and hospitalization may result in more catastrophic health expenses.…”
Section: Discussionsupporting
confidence: 73%
“…This finding was however conflicting as one of the studies found a lower odds of CHE among households that utilized health services from private facilities. Also, use of public health facilities has been associated with increased odds of CHE from other studies . This may be related to the high cost of specialized services especially in public tertiary hospitals compared with their private counterparts; hence, households tend to pay more at public health care facilities than private facilities .…”
Section: Discussionmentioning
confidence: 88%
“…All (100%) of households that received inpatient care incurred catastrophic spending in one of the studies . Hospitalization for such medical conditions are usually as emergencies and are associated with high costing diagnostic tests, treatment, and nonmedical costs such as food in addition to the low‐income level and lost earnings of the primary income earner who may be the patient or caregiver . Given the chronicity of HIV and epilepsy care, such CHE could affect continuity of care and increase mortality from these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, relevant research showed that the economic condition of migrant workers was relatively good, which may also lead to more patients choose to go to different places for medical treatment [14]. Therefore, it could be considered that people with better economic conditions were more likely to enjoy the SIMIS, while patients with poor economic conditions may choose not to see a doctor, which also causes unfairness to some extent [15,16].…”
Section: Discussionmentioning
confidence: 99%